88.3k views
5 votes
If f(x) = x2 − x − 12 and g(x) = x2 − 16, find f(x) × g(x).

User Shaheem
by
5.6k points

2 Answers

4 votes

Answer:
f(x)*g(x)=x^4-x^3-28x^2+16x+192

Explanation:

Given the function f(x) and g(x):


f(x)=x^2 - x -12\\\\g(x)= x^2 - 16

We need to multiply them. To do this we need to remember the Product of power property, which states:


(a^m)(a^n)=a^((m+n))

And the multiplication of signs:


(+)(+)=+\\(+)(-)=-\\(-)(-)=+

Then:


f(x)*g(x)=(x^2 - x -12)(x^2 - 16)\\\\f(x)*g(x)=x^4-16x^2-x^3+16x-12x^2+192

Adding like terms, we get:


f(x)*g(x)=x^4-x^3-28x^2+16x+192

User Denys Mikhalenko
by
5.9k points
5 votes

Answer:

f(x) × g(x)= x^4 - x^3 - 28x^2 + 16x + 192

Explanation:

We have the function f(x) = x^2 − x − 12 and g(x) = x^2 − 16 and we need to find the multiplication of both functions.

f(x) × g(x) = ( x^2 − x − 12)(x^2 − 16) = x^4 - 16x^2 -x^3 + 16x -12x^2 + 192

Simplifying:

f(x) × g(x)= x^4 - x^3 - 28x^2 + 16x + 192

User NickZoic
by
6.3k points